2013
DOI: 10.1021/om400702b
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Indanone from an Iridanaphthalene Complex

Abstract: The first example of evolution of an iridanaphthalene into an indanone through an intermediate indenyl is reported, serving as a good example of starting material to obtain indanones. Two new iridanaphthalenes are obtained by intramolecular C−H activation of a phenyl ring of a carbene ligand in [IrCp*{C(OMe)CHCPh 2 }(L)]PF 6 (L = PPh 2 Me, PMe 3 ) complexes. It is demonstrated that these iridanaphthalene complexes can undergo a thermal reaction to give indenyl complexes and 3-phenylindanone.M etallacyclic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…the protonated metallabenzofuran, II). [10] As yet the chemical reactivity of these metallanaphthalenes has scarcely been explored. [6] Them etalla-analogues of the simple linear polycyclic aromatic hydrocarbons (Scheme 1) are fused-ring metallabenzenes that fall under category (A).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…the protonated metallabenzofuran, II). [10] As yet the chemical reactivity of these metallanaphthalenes has scarcely been explored. [6] Them etalla-analogues of the simple linear polycyclic aromatic hydrocarbons (Scheme 1) are fused-ring metallabenzenes that fall under category (A).…”
mentioning
confidence: 99%
“…Compounds of class (B) in which one end of the fused ring is bound to the metal have been referred to as "tethered" metallabenzenes. [8,10] Only one related tricyclic metallaaromatic hydrocarbon has been reported and that is the lithium salt of ar uthenaphenanthrene oxide.T his compound, which was detected in solution spectroscopically at low temperatures,decomposes above 0 8 8C. Currently,t he only isolated examples of this type are metallanaphthalenes.T wo of the three possible isomers of these compounds (a-c, that is, metal at positions a-c in Scheme 1) have been reported.…”
mentioning
confidence: 99%
“…A small set of closely related iridanaphthalenes of isomer a have been prepared by insertion of alkenes into a benzannelated iridacyclopentadiene . In addition, metallanaphthalenes of isomer b have been prepared through oxidation of a fused‐ring iridacyclohexadiene, by rearrangement of an osmium vinyl carbyne complex, and by intramolecular C−H activation of a phenyl substituted alkenylcarbeneiridium complex . As yet the chemical reactivity of these metallanaphthalenes has scarcely been explored .…”
Section: Methodsmentioning
confidence: 99%
“…[7] In addition, metallanaphthalenes of isomer b have been prepared through oxidation of af usedring iridacyclohexadiene, [8] by rearrangement of an osmium vinyl carbyne complex, [9] and by intramolecular CÀHa ctivation of ap henyl substituted alkenylcarbeneiridium complex. [10] As yet the chemical reactivity of these metallanaphthalenes has scarcely been explored. [8,10] Only one related tricyclic metallaaromatic hydrocarbon has been reported and that is the lithium salt of ar uthenaphenanthrene oxide.T his compound, which was detected in solution spectroscopically at low temperatures,decomposes above 0 8 8C.…”
mentioning
confidence: 99%
“…In addition, we have shown that heating a solid sample of ruthenabenzene 4 at 150 °C gave a free cyclopentadienyl derivative 51 . In 2013, Bolaño and co‐workers reported the formation of an indanone starting from an α‐OMe substituted iridanaphthalene . It was proposed that the transformation involves the initial carbene migratory insertion to form the 16e intermediate AD .…”
Section: Migratory Insertion Reactionsmentioning
confidence: 95%